COMPARATIVE ANALYSIS OF GUI BASED HEALTH CARE DISEASE PREDICTION USING MACHINE LEARNING APPROACH - Reddy, E Pavan Kumar; Nalini, (International Journal of Psychosocial Rehabilitation, 2020)
Commonly, viral and mosquito borne diseases rise seasonally and regionally. Hygiene is one of the motives why a few areas in India have higher sickness rate in comparison to others .It'd be fantastic if an application may want to collect data, analyze and report to authorities. To prevent this problem in medical sectors need to predict the alert fitness illnesses (like diabetes, continual, coronary heart assault) with the aid of signs the use of gadget studying strategies. The purpose is to research device learning based strategies for disease forecasting by means of prediction effects in high-quality accuracy. The analysis of dataset by using supervised gadget mastering approach(SMLT) to seize several statistics’s like, variable identification, uni-variate evaluation, bi-variate and multi-variate evaluation, missing value remedies and analyze the data validation.